The Role Of Local Wisdom In Efforts To Prevent Stunting In Toddlers In Coastal Areas - Amelia Darwis; Rumiris Simatupang; Rahmat Pannyiwi; Edi Pramono (International Journal of Health Sciences, 2025)
Stunting is a chronic nutritional problem that remains a serious concern in Indonesia, particularly in coastal areas, which generally suffer from low levels of well-being, limited food access, and vulnerable environmental conditions. Stunting impacts not only a child's physical growth but also their cognitive development and future productivity. Furthermore, coastal communities possess a rich culture and local wisdom that can play a crucial role in maintaining food security and family nutritional status. This study aims to analyze in depth the role of local wisdom in preventing stunting in toddlers in coastal areas. This study used a qualitative approach with descriptive methods, through in-depth interviews with community leaders, mothers of toddlers, and health workers in coastal villages. Participatory observation and documentation studies were also conducted to obtain comprehensive data regarding local wisdom practices still practiced by the community. The results showed that forms of local wisdom such as the tradition of consuming fresh fish, the use of local plants (moringa leaves, sweet potatoes, bananas), and social values such as mutual cooperation and food arisan (social gatherings) have a significant contribution to preventing stunting . This local wisdom supports the fulfillment of balanced nutrition, strengthens social solidarity, and raises awareness of the importance of a healthy diet for toddlers. Modernization, changing consumption patterns, and coastal environmental degradation threaten the sustainability of these practices. Therefore, integrating local wisdom into government programs such as Posyandu (Integrated Health Posts), PKK (Family Welfare Movement), and nutrition education is necessary to strengthen culturally based stunting prevention strategies. Therefore, preserving and revitalizing local wisdom can be a sustainable solution to reducing stunting prevalence in Indonesia's coastal areas.